Final girl : Halloween [videorecording (DVD)] - Arguello, Andrew; Palo, MJ; Palo, MJ; Lynn, Krystal; Locricchio, Ragen; Winters, Grace (Filmhub, 2024)
The sole survivor of a slasher killer's murderous spree struggles to overcome her grief while a new killer is ravaging the town and her friends.